Stoneover: the observed lessons and unanswered questions of cannabis legalization - Anguelov, Nikolay; Moyer, Jeffrey (Lexington Books, 2022)
Introduction -- Political polarization and cannabis legalization by Paul Musgrave and Clyde Wilcox -- The cannabis strain : marijuana prohibition in an age of police defunding by Robert Hardaway -- Seeing through the haze : using intersectionality to reveal systematic differences in support for marijuana decriminalization by Geoffrey Whitebread -- The politics of marijuana, immigration, and Latinos by Joe R. Tafoya and Melissa R. Michelson -- Implementing social equity : opportunities and challenges from marijuana legalization in Massachusetts by Jeffrey Moyer -- Bureaucratic structures and policy implementation challenges in medical cannabis by Céline Mavrot -- Consumer well-being and cannabis spending habits : evidence from Massachusetts by D. Steven White, Catharine M. Curran, Paul Bacdayan, and Marion McNabb -- Exaggerated panic or valid concerns? Post-legalization youth drug use by Renee Scherlen and José Antonio Cisneros-Tirado -- Using administrative and survey data to evaluate the impact of changing marijuana laws and policies on marijuana use, treatment admissions for marijuana, and mortality related to marijuana and other drug use by Maggie Martin, Rebecca Ivester, Jesse Mishra, Maryam Salihu, Sonja Richard and Ryan Kling -- The unintended consequences of marijuana decriminalization on illegal commerce and the opioid crisis by Nikolay Anguelov, Michael P. McCarthy and Thalia Valkanos.